The principle of providing effective legal protection to citizens in the enforcement procedure and dejudicialization of the executive court function in favor of the bailiff (example of Serbian law) - Petrović, Stojana Đ. (Glasnik Advokatske komore Vojvodine, 2021)
Increasing the efficiency of the enforcement procedure was the main motive for introducing the enforcement agent into the law of Serbia, but also into the law of the surrounding countries. Although the first executors in Serbia were appointed in 2012, so far no study has been published in the theoretical public, based on scientific methodology, on whether the Serbian legislator managed to achieve this set goal. The procedural theory is still mostly based on the assumption that the transfer of judicial procedural powers to bailiffs has contributed to the efficiency of the enforcement procedure, compared to the previous (in) efficiency of the courts. In this paper, using the CEPEJ methodology, and determining statistically significant correlations of individual efficiency variables, expressed by the values ​​of Pearson’s number, on the example of enforcement agents appointed in the courts in Serbia, it was investigated whether the enforcement rate was achieved, whether it was achieved an acceleration of the enforcement procedure, and whether the number of unresolved cases has been reduced, which would indicate their efficiency in the procedures in which they decide on the permit for enforcement and carry out enforcement. The obtained values ​​of the observed variables indicate that the legislator in Serbia, by introducing enforcement agents, did not achieve the promised efficiency of the enforcement procеdure